More than one and less than many: Materialising hepatitis C and injecting drug use in self-help literature and beyond - Fraser, Suzanne (The Australian Sociological Association, 2010)
Knowledge about disease and illness usually emerges as a result of complex social negotiations among those with a stake in the outcomes of this knowledge. These negotiations can involve a range of agents and discursive avenues, some of which are contradictory and paradoxical. This is especially true for the blood-borne virus hepatitis C, the medical, social and political features of which - associations with injecting drug use, 'tainted blood' scandals and HIV - render it a controversial disease involving a range of highly motivated stakeholders. In this paper I analyse one such set of agents in the process of disease knowledge negotiation: self-help books on hepatitis C. In conducting this analysis I offer insights into the content of the books and the way they construct hepatitis C and those who have it. I do this by mapping three key issues helping to shape the way hepatitis C is constituted in these books: HIV, injecting drug use and iatrogenic (medically caused) transmission, and by exploring the implications of the themes of emotion, risk and guilt that arise in the playing out of these issues. In the process I aim to make sense of the complexity of disease, its social constitution and its role in shaping social phenomena such as stigma.